СALCIUM DEFICIENCY IN CHILDREN: POSSIBLE SOLUTIONS - N.I. Taibulatov (Union of pediatricians of Russia, 2008)
The article is devoted to the problem of modern pediatrics - child calcium deficiency. The author studies certain aspects of bone tissue metabolism and proves that alimentary calcium deficiency during periods of both prenatal and postnatal development might lead to various pathologies of locomotor system. The article also provides recommendations on optimizing microelement and vitamin replenishment during the periods of increased consumption.Key words: calcium, deficiency, treatment, prophylaxis, children.